Methylhydrazine Lone‐Pair Engineering for Polar Lead‐Free Perovskite Enables Self‐Powered X‐Ray Detection - Ruiqing Li; Jianbo Wu; Zeng‐Kui Zhu; Yaru Geng; Xinling Li; Yifei Wang; Bohui Xu; Zheshuai Lin; Junhua Luo (Small Science)
Lead‐free A3Bi2I9‐type perovskites demonstrate excellent performance in direct X‐ray detection owing to their high bulk resistivity and reduced ion migration. However, the reported centrosymmetric A3Bi2I9 can only operate with external voltage, inevitably resulting in energy consumption and bulky monolithic circuits, limiting their further development. Herein, exploiting the methylhydrazine (MHy) cation with 2s2 lone‐pair electrons (LPEs), a chiral‐polarity perovskite MHy3Bi2I9 are obtained and explored its self‐powered X‐ray detection properties. Where MHy forms the strong hydrogen bond interaction with the inorganic framework, resulting in the asymmetric Bi2I9 unit. Meanwhile, the 2s2 LPEs contribute to generating MHy dipole moments, leading to spontaneous polarization. On the one hand, spontaneous polarization acts as a driving force to realize the X‐ray‐generated carriers’ separation and transport to acquire self‐powered detection ability. On the other hand, the reduced noise current and dark current under zero bias further increase the signal‐to‐noise ratio and lower the detection limit. Notably, the MHy3Bi2I9 single‐crystal‐based detector displays a considerable sensitivity (106 μC Gy−1 cm−2) and an ultralow detection limit (55 nGy s−1) in self‐powered mode. Herein, new insights for constructing polar lead‐free perovskite and realizing unprecedented A3Bi2I9‐type self‐powered X‐ray detectors are provided.